A new classification of the tribe Hygrotini Portevin, 1929 (Coleoptera: Dytiscidae: Hydroporinae) - Villastrigo, Adrián; Ribera, Ignacio; Manuel, Michaël; Millán, Andrés; Fery, Hans (Zootaxa, 2017)
The tribe Hygrotini Portevin, 1929 is currently composed of four genera, Heroceras Guignot, 1950, Herophydrus Sharp, 1880, Hygrotus Stephens, 1828 (with two subgenera, Coelambus Thomson, 1860, and Hygrotus s. str.), and Hyphoporus Sharp, 1880. A recent molecular phylogeny of the tribe with ca. 45% of the 137 described species of Hygrotini, including the type species of all genus-level taxa, revealed extended para- or polyphyly of the current genera and subgenera (Villastrigo et al., Zoologica Scripta, in press), for which reason a new classification of the tribe Hygrotini is proposed. Within Hygrotini only two genera are recognised: Clemnius n. gen. (with two subgenera: Clemnius s. str. with type species Hyphydrus decoratus Gyllenhal, 1810, and Cyclopius n. subgen. with type species Hydroporus acaroides LeConte, 1855) and Hygrotus (with four subgenera: Coelambus, Hygrotus s. str., Hyphoporus n. stat. and Leptolambus n. subgen. with type species Dytiscus impressopunctatus Schaller, 1783). Two genera are synonymised under Hygrotus s. str., Herophydrus n. syn. and Heroceras n. syn. The following 67 new combinations, for species thus far treated under the genera Heroceras, Herophydrus, Hygrotus and Hyphoporus, result from the new classification: Clemnius (s. str.) berneri (Young & Wolfe, 1984) n. comb., Clemnius (s. str.) decoratus (Gyllenhal, 1810) n. comb., Clemnius (s. str.) hydropicus (LeConte, 1852) n. comb., Clemnius (s. str.) laccophilinus (LeConte, 1878) n. comb., Clemnius (s. str.) sylvanus (Fall, 1917) n. comb., Clemnius (Cyclopius) acaroides (LeConte, 1855) n. comb., Clemnius (Cyclopius) farctus (LeConte, 1855) n. comb., Clemnius (Cyclopius) marginipennis (Blatchley, 1912) n. comb., Hygrotus (s. str.) assimilis (Régimbart, 1895) n. comb., H. (s. str.) bilardoi (Biström & Nilsson, 2002) n. comb., H. (s. str.) capensis (Régimbart, 1895) n. comb., H. (s. str.) confusus (Régimbart, 1895) n. comb., H. (s. str.) descarpentriesi (Peschet, 1923) n. comb., H. (s. str.) discrepatus (Guignot, 1954) n. comb., H. (s. str.) endroedyi (Biström & Nilsson, 2002) n. comb., H. (s. str.) gigantoides (Biström & Nilsson, 2002) n. comb., H. (s. str.) gigas (Régimbart, 1895) n. comb., H. (s. str.) goldschmidti (Pederzani & Rocchi, 2009) n. comb., H. (s. str.) gschwendtneri (Omer-Cooper, 1957) n. comb., H. (s. str.) hyphoporoides (Régimbart, 1895) n. comb., H. (s. str.) ignoratus (Gschwendtner, 1933) n. comb., H. (s. str.) inquinatus (Boheman, 1848) n. comb., H. (s. str.) janssensi (Guignot, 1952) n. comb., H. (s. str.) kalaharii (Gschwendtner, 1935) n. comb., H. (s. str.) morandi (Guignot, 1952) n. comb., H. (s. str.) muticus (Sharp, 1882) n. comb., H. (s. str.) natator (Biström & Nilsson, 2002) n. comb., H. (s. str.) nigrescens (Biström & Nilsson, 2002) n. comb., H. (s. str.) nodieri (Régimbart, 1895) n. comb., H. (s. str.) obscurus (Sharp, 1882) n. comb., H. (s. str.) obsoletus (Régimbart, 1895) n. comb., H. (s. str.) ovalis (Gschwendtner, 1932) n. comb., H. (s. str.) pallidus (Omer-Cooper, 1931) n. comb., H. (s. str.) pauliani (Guignot, 1950) n. comb., H. (s. str.) quadrilineatus (Régimbart, 1895) n. comb., H. (s. str.) reticulatus (Pederzani & Rocchi, 2009) n. comb., H. (s. str.) ritsemae (Régimbart, 1889) n. comb., H. (s. str.) rohani (Peschet, 1924) n. comb., H. (s. str.) rufus (Clark, 1863) n. comb., H. (s. str.) sjostedti (Régimbart, 1908) n. comb., H. (s. str.) spadiceus (Sharp, 1882) n. comb., H. (s. str.) sudanensis (Guignot, 1952) n. comb., H. (s. str.) travniceki (Šťastný, 2012) n. comb., H. (s. str.) tribolus (Guignot, 1953) n. comb., H. (s. str.) variabilis secundus (Régimbart, 1906) n. comb., H. (s. str.) variabilis variabilis (Guignot, 1954) n. comb., H. (s. str.) verticalis (Sharp, 1882) n. comb., H. (s. str.) vittatus (Régimbart, 1895) n. comb., H. (s. str.) wewalkai (Biström & Nilsson, 2002) n. comb., Hygrotus (Hyphoporus) anitae (Vazirani, 1969) n. comb., H. (Hyphoporus) aper (Sharp, 1882) n. comb., H. (Hyphoporus) bengalensis (Severin, 1890) n. comb., H. (Hyphoporus) bertrandi (Vazirani, 1969) n. comb., H. (Hyphoporus) caliginosus (Régimbart, 1899) n. comb., H. (Hyphoporus) dehraduni (Vazirani, 1969) n. comb., H. (Hyphoporus) elevatus (Sharp, 1882) n. comb., H. (Hyphoporus) geetae (Vazirani, 1969) n. comb., H. (Hyphoporus) josephi (Vazirani, 1969) n. comb., H. (Hyphoporus) kempi (Gschwendtner, 1936) n. comb., H. (Hyphoporus) montanus (Régimbart, 1899) n. comb., H. (Hyphoporus) nilghiricus (Régimbart, 1903) n. comb., H. (Hyphoporus) oudomxai (Brancucci & Biström, 2013) n. comb., H. (Hyphoporus) pacistanus (Guignot, 1959) n. comb., H. (Hyphoporus) pugnator (Sharp, 1890) n. comb., H. (Hyphoporus) severini (Régimbart, 1892) n. comb., H. (Hyphoporus) subaequalis (Vazirani, 1969) n. comb., H. (Hyphoporus) tonkinensis (Régimbart, 1899) n. comb.